The Influence of GDP, Third Party Funds, and Non-Performing Loans on Credit Procyclicality Behavior in Government Banks - Nabila Putri Naisya; Nurbetty Herlina Sitorus (Lafadz Jaya Publisher, 2024)
This research aims to determine the influence of GDP, Third Party Funds, and Non-Performing Loans on credit procyclicality behavior at Government Banks. The method and analytical tools used in this research are panel data regression with the dependent variable, namely Credit, and the independent variables, namely GDP, Third Party Funds, and Non-Performing Loans. The scope of this research is BUMN Banks with a time span of 2017-2022. This research shows that the best model chosen is the Fix Effect Model with the results that GDP, Third Party Funds and Non-Performing Loans have a positive and significant effect on credit distribution, which shows that there is procyclical behavior in government banks.